+0  
 
0
236
1
avatar

-(3)/(4)(2-2x)^(2)

Guest Oct 27, 2017

Best Answer 

 #1
avatar+7324 
+1

-(3)/(4)(2 - 2x)^(2)          Expand  (2 - 2x)2 .

 

=  -(3)/(4)(2 - 2x)(2 - 2x)

 

=  -(3)/(4)(4 - 8x + 4x2)

 

=  -(3)/(4)(4 - 8x + 4x2)        Distribute the  3/4 .

 

=  -[ (3/4)(4) - (3/4)(8x) + (3/4)(4x2) ]

 

=  -[ 3 - 6x + 3x2 ]

 

=  -3 + 6x - 3x2

 

=  -3x2 + 6x - 3

hectictar  Oct 27, 2017
 #1
avatar+7324 
+1
Best Answer

-(3)/(4)(2 - 2x)^(2)          Expand  (2 - 2x)2 .

 

=  -(3)/(4)(2 - 2x)(2 - 2x)

 

=  -(3)/(4)(4 - 8x + 4x2)

 

=  -(3)/(4)(4 - 8x + 4x2)        Distribute the  3/4 .

 

=  -[ (3/4)(4) - (3/4)(8x) + (3/4)(4x2) ]

 

=  -[ 3 - 6x + 3x2 ]

 

=  -3 + 6x - 3x2

 

=  -3x2 + 6x - 3

hectictar  Oct 27, 2017

31 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.